(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
The present investigation described the effective preparation of glucosamine hydrochloride (GluHCl) from chitin which was extracted from indigenous shrimp shell. GluHCl has attracted much attention owing to its therapeutic activity in osteoarthritis and widely used dietary supplement. The key step involved was extraction of chitin from shrimp skeleton and then hydrolysis of chitin by concentrated hydrochloric acid. The reaction proceeds via break down of glycoside linkage. Structural analysis was carried out by melting point, TLC, FT-IR, elemental analysis and all the data were compared with that of standard GluHCl. The elemental (C, 32.75; H, 6.51; N, 6.20) analysis is good concord with the calculated value (C, 33.42; H, 6.54; N, 6.50). Absence of v max at 1726 cm-1 indicates that GluHCl is a deacetylated product of chitin. The yields of the product mainly depend on reaction conditions. Maximum yield (63.5%) was obtained when chitin was hydrolyzed with concentrated HCl for 1.30 h. Key words: Shrimp shell; Chitin, Acid hydrolysis; Glucosamine hydrochloride Osteoarthritis. DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9046 BJSIR 2011; 46(3): 375-378